2020
DOI: 10.1186/s12882-020-02035-w
|View full text |Cite
|
Sign up to set email alerts
|

Urine neutrophil gelatinase-associated lipocalin and urine output as predictors of the successful discontinuation of continuous renal replacement therapy in critically ill patients with acute kidney injury

Abstract: Background: Continuous renal replacement therapy (CCRT) is a frequently used modality for the support of intensive care patients with acute kidney injury (AKI). Nevertheless, there are no objective criteria for the discontinuation of CRRT. The purpose of this study was to investigate whether urine neutrophil gelatinase-associated lipocalin (uNGAL) alone or in combination with urine output could be used as a diagnostic test for renal function recovery in ICU patients on CRRT. Methods: This was a single-centre p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Urine NGAL has been proven to have good utility for predicting short-term and long-term kidney function reversal [32][33][34]. Yet, no significant difference in urine NGAL levels existed between the recovery and nonrecovery groups in the present study (Fig.…”
Section: Relationship To Previous Studiescontrasting
confidence: 51%
“…Urine NGAL has been proven to have good utility for predicting short-term and long-term kidney function reversal [32][33][34]. Yet, no significant difference in urine NGAL levels existed between the recovery and nonrecovery groups in the present study (Fig.…”
Section: Relationship To Previous Studiescontrasting
confidence: 51%
“…Twenty-two of the 54 patients recovered renal function defined as dialysis independency at 72 h, while 32 did not. With a predictive value of 93% the combination of urine NGAL at 6 h after CRRT cessation and the 24-h UO prior to CRRT cessation proved to be the best diagnostic test for CRRT liberation [ 38 ].…”
Section: Predictive Ability Of Traditional Surrogate Markers Of Renal Function or Novel Kidney Biomarkers For Recovery Of Sufficient Renamentioning
confidence: 99%
“…We observed here a similar result in urinary NGAL. Stads et al and Thomsen et al also demonstrated the predictive value of urinary NGAL on CVVHDF discontinuation [ 29 , 30 ]. The former study included 92 patients and reported that urinary NGAL was higher in the unsuccessful group.…”
Section: Discussionmentioning
confidence: 99%